Supramolecular Nanofibers Enhance Growth Factor Signaling by Increasing Lipid Raft Mobility - Newcomb, Christina J. (Nano Lett, 2016)
[Image: see text] The nanostructures of self-assembling biomaterials have been previously designed to tune the release of growth factors in order to optimize biological repair and regeneration. We report here on the discovery that weakly cohesive peptide nanostructures in terms of intermolecular hydrogen bonding, when combined with low concentrations of osteogenic growth factor, enhance both BMP-2 and Wnt mediated signaling in myoblasts and bone marrow stromal cells, respectively. Conversely, analogous nanostructures with enhanced levels of internal hydrogen bonding and cohesion lead to an overall reduction in BMP-2 signaling. We propose that the mechanism for enhanced growth factor signaling by the nanostructures is related to their ability to increase diffusion within membrane lipid rafts. The phenomenon reported here could lead to new nanomedicine strategies to mediate growth factor signaling for translational targets.